National and international recognitions to research projects of UMP - Noor Syahidah, Sabran (Penerbit UMP, 2014)

(untitled)
Universiti Malaysia Pahang (UMP) took part in various research project exhibitions and competitions that have elevated the university's positional name at the national and international level.